Perception of Justice in Performance Appraisal and Effect on Satisfaction: Empirical Findings from Northern Cyprus Banks - Ibeogu, Patrick Henry; Öztüren, Ali (Elsevier, 2015)
Appraisals could be problematic; nevertheless they are deemed as necessary in organizational management. This is because workers might not always view appraisals as a positive measure. When the employees perceive appraisals to be fair, it emits positive attitude and vice versa. This study aimed to understand the perceptions of employees towards performance appraisals. Data (n=100) was gathered through questionnaires and administered to workers in the banks of Northern Cyprus. An overall perception of respondents shows a positive rating towards interpersonal justice, distributive justice and procedural justice in performance appraisal (PA). While the respondents agreed to rating PA system positively, metrics that define high satisfaction with the PA system was statistically low and non-significant. This can be due to the fact that the majority of these staff perceives PA to be compulsory or organizational routines, and did not evidently see how it affects their job or their career. Furthermore, satisfaction with PA system can only be translated when the employees see that a positive appraisal results in pay rise, promotion, training and development, awards, other monetary incentives such as benefits and insurance.
The file in this item is the publisher version (published version) of the article.
Keywords: Performance Appraisal; Justice; Employee Satisfaction; Northern Cyprus Banking Industry